Determination of SPF (Sun Protection Factor) Value in Sunscreen Formulation of Vetiveria Zizanioides L. Essential Oil - Waode Suiyarti; Ervianingsih; Chitra Astari; Riska; Sunarto S (Postgraduate, University of Mataram, 2025)
This research aimed to determine the in vitro Sun Protection Factor (SPF) value of sunscreen formulations containing vetiver essential oil (Vetiveria zizanioides) at various concentrations. Vetiver essential oil is known to possess various biological activities, including potential as a UV protective agent. Oil-in-water emulsion-based sunscreen formulations were prepared with varying concentrations of vetiver essential oil (1%, 3%, and 5% v/v). The SPF value was determined spectrophotometrically using the in vitro method. The physicochemical characteristics of the formulations (viscosity and pH) were also evaluated. The results showed that the addition of vetiver essential oil tended to significantly increase the SPF value of the sunscreen formulations with increasing concentration. The formulation with a 5% concentration of vetiver essential oil exhibited the highest SPF value. The physicochemical characteristics of the formulations were still within the acceptable range for topical preparations. This research indicates the potential of vetiver essential oil as a natural UV protective agent in sunscreen formulations.